DYNAMIC OF DORMANCY AND CARBOHYDRATE AND PROTEIN CONTENT IN VEGETATIVE BUDS AND STEMS WITH ONE AND TWO YEARS OLD OF APPLE TREE WITH OR WITHOUT SUPPLEMENTARY CHILL - de CARVALHO, Ruy Inacio Neiva (Scientia Agraria, 2002)
This work aimed to evaluate the dynamic of dormancy and carbohydrate and protein contents in buds and stems with one and two years old of apple tree cv Imperial Gala with or without supplementary chill, collected in a high density orchard. The samples were collected in Porto Amazonas/Paraná/Brazil in intervals of 21 days from april to august, 2000. The variation of dormancy intensity was observed by the biological test of single node cuttings. The stems collected were treated or not with 1.440 h of chill (4 to 7° C). Buds and stems were analysed separately to the determination of the carbohydrate and protein content. The variations of humidity and the Ca, Mg and P content and morphological aspects were also analysed in buds and stems. The experiments were realized in randomized blocks design for factor chill, with factor date of collect a split plot on chill. Three replications were made to carbohydrate and protein content and four replications were made to biological test. The contents of glucose, frutose and sorbitol are also determined. The internal morphology of two years old buds characterized a small development of a stem inside the bud, with the meristematic region located more distant from the insertion of the bud in the stem. One year old buds presented a more intense dormancy in July, while to two years old buds this fact occur at the end of May, however without a defined peak. The supplementary chill was effective to reduce the average time to burst of one and two years old buds. There was a variation in the carbohydrate and protein content during the period of apple buds dormancy and the dynamics of the variations were independents. The dynamic of carbohydrate content was altered by the supplementary chill but the dynamic of protein content was not. Sorbitol was the main carbohydrate in the buds and stems of apple tree from May to August and the carbohydrate that presented the more significant variations after the treatment with cold temperatures, mainly in the begining of dormancy. Although the total soluble carbohydrate content in the one year old buds decreased, occurred an accumulation of glucose and frutose during the dormancy. The chill treatment during the dormancy period (from May to July) promoted the more significant variations in the soluble carbohydrate content. The chill treatment during the end of dormancy (from July to August) promoted less intense variations in the soluble carbohydrate content.